PROFIL KOMUNIKASI MATEMATIS SISWA KELAS X MIPA MA NEGERI 2 KOTA PALU DALAM MENYELESAIKAN SOAL CERITA SISTEM PERSAMAAN LINEAR TIGA VARIABEL : Profile of Mathematical Communication of The 10th Grade of Mipa MA Negeri 2 Palu City in Completing Essays of System of Linear Equation In Three Variables - Nurlela Sari; Muh. Hasbi; Anggraini Anggraini (Universitas Tadulako, 2025)
This research aims to obtain students' mathematical communication profile in solving story problems of three-variable linear equation system. This type of research is descriptive research with a qualitative approach. The research subjects consisted of 3 students each with high, medium and low abilities. Data were collected using 2 techniques, namely written task and interviews. Indicators of mathematical communication in this research use indicators of mathematical communication according to NCTM. The results showed: (1) in indicator of expressing mathematical ideas through writing and spoken, MRH and NNP subjects wrote and explained the example and how to form a linear equation of three variables. While HFK only explained the example. HFK also wrote and explained how to form a linear equation of three variables; (2) in indicator of understanding, interpreting, and evaluating mathematical ideas in writing and spoken, MRH and NNP subjects wrote and explained the steps of solving the problem correctly, while HFK was incomplete in writing and explaining it. MRH and NNP wrote and mentioned the conclusion according to what was asked in the problem, while HFK did not write or mention it; (3) In indicator of using mathematical terms, symbols and structures to model mathematical situations or problems, MRH, NNP and HFK used mathematical symbols and structures in writing example, equations and problem solving steps.